Performance evaluation of an ejector-based cooling system - Neo, Tiffany Bi Xuan. (2013)
With limited land for agriculture, Singapore's food resource largely depends on imports from various countries. A key consideration that takes place is how to keep those food fresh between the time it reaches our shores and before it can be kept in the refrigerator in the supermarket or at home. Multi-evaporator refrigeration system (MERS) then comes into play, as it provides an environment for food to stay fresh even during long periods of storage or transportation in the vehicle.